Kenya : Second Reviews Under the Stand-by Arrangement and the Arrangement Under the Standby Credit Facility, and Requests for a New Twenty-Four Month Stand-By Arrangement, and a New Twenty-Four Month Arrangement Under the Standby Credit Facility-Press Release; Staff Report; and Statement by the Executive Director for Kenya. (IMF Staff Country Reports; Country Report, 2016)
This paper presents an overview of Kenyan economic development. It discusses recent economic development, outlook, and risks related to Kenyan economy, as well as policy and structural reforms. Although Kenya's macroeconomic performance remains robust, external shocks complicated achievement of some program's macroeconomic objectives. In light of persistent external risks and a weaker outlook, the authorities have requested continued program engagement with the IMF under new 24-month Stand-By Arrangement and Standby Credit Facility (with access of 130.67 percent and 65.33 percent of quota, respectively). The new program includes a comprehensive package of measures targeting a significant reduction in vulnerabilities, paving the way for an eventual exit from IMF arrangements.